Medication Errors in Secondary Care Hospitals in Kuwait: The Perspectives of Healthcare Professionals - Alsaleh, Fatemah M.; Alsaeed, Sara; Alsairafi, Zahra K.; Almandil, Noor B.; Naser, Abdallah Y.; Bayoud, Tania (Frontiers in Medicine, 2021)
Objectives: Medication errors (MEs) are the most common cause of adverse drug events (ADEs) and one of the most encountered patient safety issues in clinical settings. This study aimed to determine the types of MEs in secondary care hospitals in Kuwait and identify their causes. Also, to determine the existing system of error-reporting in Kuwait and identify reporting barriers from the perspectives of healthcare professionals (HCPs). Material and Methods: A descriptive cross-sectional study was conducted using a pre-tested self-administered questionnaire. Full-time physicians, pharmacists, and nurses (aged 21 years and older) working in secondary governmental hospitals in Kuwait were considered eligible to participate in the study. Descriptive statistics were used to analyse the data. Results: A total of 215 HCPs were approached and asked to take part in the study, of which 208 agreed to participate giving a response rate of 96.7%. Most HCPs (n=129, 62.0%) reported that the most common type of MEs is “prescribing error”, followed by “compliance error” (n=83; 39.9%). Most HCPs thought that high workload and lack of enough breaks (n=128; 61.5%) are the most common cause of MEs, followed by miscommunication either among medical staff themselves or between staff and patients, which scored (n=89; 42.8%) and (n=82; 39.4%), respectively. In the past 12 months, 77.4% (n=161) of HCPs reported that they did not fill out any ME incident reports. Lack of feedback (n=65; 31.3%), as well as the length and complexity of the existing incident reporting forms (n=63; 30.3%) were the major barriers against reporting any identified MEs. Conclusions: MEs are common in secondary care hospitals in Kuwait and are shown during many stages of practice. HCPs suggested many strategies to help reducing MEs, mainly, proper communication between HCPs; double-checking every step of the process before administering medications to patients; providing training to keep HCPs up to date on any new treatment guidelines; and to computerize health systems.